2017
DOI: 10.1371/journal.pone.0183675
|View full text |Cite|
|
Sign up to set email alerts
|

Elevation in and persistence of multiple urinary biomarkers indicative of oxidative DNA stress and inflammation: Toxicological implications of maleic acid consumption using a rat model

Abstract: Maleic acid (MA), an intermediate reagent used in many industrial products, instigated public health concerns in Taiwan when it was used to adulterate an array of starch-based delicacies to improve texture and storage time. Established studies reported that exposure to high concentrations of MA induce renal injury; little is known whether oxidative stress is induced at a relative low dose. This study aims to investigate the effect of oral single dose exposure of MA on the status of oxidative stress and inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Oxidative stress plays an important role in ischemic myocardial injury, and elevated levels of ROS have been detected in ischemic myocardium (Misra et al 2009). Several studies have reported that butyric acid, maleic acid, and malonic acid cause oxidative stress and fumaric acid was an endogenous antioxidant compound (Laborde et al 2014;Maragos et al 2004;Wu et al 2017). Thus, increased butyric acid, maleic acid, and malonic acid and decreased fumaric acid can have an important role in ischemic myocardial injury and may be related to the degree of ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress plays an important role in ischemic myocardial injury, and elevated levels of ROS have been detected in ischemic myocardium (Misra et al 2009). Several studies have reported that butyric acid, maleic acid, and malonic acid cause oxidative stress and fumaric acid was an endogenous antioxidant compound (Laborde et al 2014;Maragos et al 2004;Wu et al 2017). Thus, increased butyric acid, maleic acid, and malonic acid and decreased fumaric acid can have an important role in ischemic myocardial injury and may be related to the degree of ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…The authors wish to clarify the relationship between this PLOS ONE article (a single-dose study) [ 1 ] and a closely related repeated-dose toxicity study published in July 2017 in the Journal of Applied Toxicology [ 2 ]. Findings discussed in this PLOS ONE article [ 1 ] focus on oxidative stress induction and persistence after single-dose oral (gavage) exposure to maleic acid (MA), elucidating the kinetics of oxidant burden formation and clearance. In the Journal of Applied Toxicology study [ 2 ], the authors investigate the effects of repeated exposure to MA in rats, using 1 H nuclear magnetic resonance analysis to focus on changes in the metabolic profile.…”
mentioning
confidence: 99%
“…In fact, the authors found no significant histological changes in liver and kidney tissue at seven days in rats administered a single dose of MA as compared to untreated controls. The authors mention “histopathological observations” in the last sentence of the Discussion in [ 1 ], referring to results of analyses that were not included in the manuscript. The latter part of the last sentence should therefore be omitted.…”
mentioning
confidence: 99%